MULTICRITERIA DECISION-MAKING IN THE SELECTION OF WARSHIPS: A NEW APPROACH TO THE AHP METHOD - Santos, Marcos dos; Costa, Igor Pinheiro de Araujo; Gomes, Carlos Francisco Simões (International journal of the analytic hierarchy process, 2021)
The budgetary constraints for the Brazilian Navy (BN) have caused several negative effects, resulting in an undersized fleet, decreasing the capacity to protect marine oil and natural gas fields, combat marine pollution from ships, and monitor other illegal activities at sea and inland waters. This paper aims to choose a medium-sized warship to be built by the BN, through the application of the Analytic Hierarchy Process (AHP) method. After a bibliometric study on Multiple-Criteria Decision-Making (MCDM), the AHP was chosen as the most appropriate method for the proposed case study. We analyzed three ship projects with regard to nine operational and economic criteria, taking into account the evaluations of BN officers with recognized experience and knowledge in military operations. We also introduced a sensitivity analysis based on the relationship between standard deviation and mean scores in order to verify and increase the reliability of the ranking. As a result, the methodology suggested that the best option is to build a brand-new ship with more significant modernizations to provide for the operational needs of the BN.